CROP RESIDUE AS OPTIMUM FEED SOURCING FOR LIVESTOCK KEPT UNDER FREE RANGE CONDITIONS WITHIN THE BLUE NILE BASIN OF SUDAN - Ahmed, Muna; H.K., Donia; E. M, El Digair (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
The present study was initiated show that the best feed sourcing for animal production could crop-livestock under rangeland conditions of arid environment within the Nile basin ecosystem. For crop-livestock production systems, livestock water productivity (LWP) was used to indicate water utilized by the animal converted to useful products. Parameters measured were: biomass availability from rangelands and crop residues, supply versus demand for the different animal species and treated crop residues to improve animal performance. Trends in rangeland productivity, crop residue biomass and animal’s number and herd structure were measured through the years 2014 – 2018 in seven localities of Sennar state. Total biomass in the form of crop residues and biomass from range was calculated to determine the livestock demands during the dry season; this was done by utilizing Tropical livestock unit (TLU) equivalents and basal metabolic rates. Rangeland status was estimated using remote sensing. using multiple sets of Sentinel-2 and Landsat images (in case of cloud cover in the Sentinel-2 image). Crop production was projected for the summer season from the ‘Ministry of Agriculture’, Further available crop residues were calculated as: 1kg sorghum seed gives 3kg sorghum straw, 1kg millet seed gives 3 kg straw, 1kg ground nut pod gives 2kg straw. The biomass demand was calculated based on the data from Arab Organisation for Agricultural Development that annual animal unit demand is 2.4 tons. This was translated to the biomass demand of approximately 6.5 kg per day per animal unit. The International Livestock Research Institute (ILRI) estimation of animal maintenance energy of 11,000 Kcal per LTU per day for grazing cattle in Africa, for maintenance energy, would require about 5 kg per tropical livestock unit per day of feed for maintenance. The amount of evapotranspiration required to produce this feed would be about 1.25 cubic meters per TLU per day or 450 cubic meters per tropical livestock unit per year. This compares with 25–50 liters a day or 9–18 cubic meters per tropical livestock unit per year for drinking water. Hence for each locality biomass demand was calculated as: No. of AU in the locality x 6.5 kg dry matter/day. Animal experimentation utilized 2 dairy goats fed with straws treated with 5% urea and Student t-test was used to obtain the significance between the control and treated animals. The results showed that contribution of crop residue to the biomass was very important and increased over the years for Abu Hougar it was maintained around 90%, for El Dali increased from 3% to 888% in year 2018. For El Dinder, El Souki and Sinnar increased to reach 454%, 775%, 219% respectively in the year 2018. However, Singa showed a decline in crop residue from 526 to 163%. Availability of the biomass showed high variability among the localities. Animal’s number changed slightly over the years. Except for Sharg Sinnar. Sheep population was the highest while camels were the lowest in all localities, but herd structure was not the same where cattle, sheep and goats were comparable at El Souki and Singa. Camels and goats were comparable in El Dinder only. Abu Hougar and El Dali showed lower population of cattle and goats. At Sinnar, goats and cattle population was nearly the same. Sharg Sinnar showed comparable ratios for sheep, cattle and goats. As for animal experimentation where dairy goats were used to test the crop residue treated with urea on food intake and milk yield, it was found that while food intake decreased significantly (P<0.05), milk yield increased significantly (P<0.001). It could be concluded that for crop livestock-water ecological system, crop residues as feed sourcing is considered the optimum biomass supply for animals during the summer season where there is no additional water is required, livestock water productivity (LWP) could be increased with better management of soildegradation, water runoff and rangeland conservation.